Legal Analysis Of Compensation Claim In Australia-Indonesia Maritime Delimitation Zone Belongs To Unclos 1982 - Ninne Zahara Silviani (Journal of Judicial Review, 2018)
Oil spill on the water column of the sea could rise a marine polluting and affect many aspects of living. The water column in Indonesia-Australia Delimitation zone which under Indonesia sovereignty is polluted when the montara offshore exploded and the oil spilled through the ocean and reached Indonesia coastal area in East Nusa Tenggara. Based on UNCLOS 1982, PTTEP Australasia has violated the Part XII of UNCLOS 1982 about protection and preservation of the marine environment and responsible for Sea polluting on the water column of Indonesia. Indonesian Government could prove the occurrence of marine pollution in Australia-Indonesia Maritime Delimitation zone that conducted by PTTEP Australasia and Indonesia government could submit a lawsuit and sue PTTEP Australasia to the Central Jakarta District Court due to oil spill polluting at Indonesia-Australia Maritime Delimitation zone belongs to UNCLOS 1982. This article showed the data of Indonesian researchers due to this pollutingand how Indonesia government has rights to submit a lawsuit against PTTEP Australasia and its mother company to Central Jakarta District court belongs to UNCLOS 1982.